2023
DOI: 10.1186/s12882-023-03065-w
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from high glucose-treated macrophages promote epithelial–mesenchymal transition of renal tubular epithelial cells via long non-coding RNAs

Abstract: Background Macrophages contribute to epithelial–mesenchymal transition (EMT) in diabetic nephropathy (DN). Exosomal long non-coding RNAs (lncRNAs) derived from macrophages play a major role in transmitting biological information, whereas related studies on DN are rare. Here we investigated the effects of exosomal lncRNAs from high glucose-treated macrophages on EMT. Methods High glucose-treated macrophage exosomes (HG-exos) were extracted by coprec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…anti-CIRC was used for further research owing to its higher knockdown efficiency. The designed siRNA should specifically aim to hsa_circ_0005519, to avoid any interference with its linear host gene [ 16 ]. Notably, the siRNAs in this study showed no effects on expression of SNX13 mRNA (hsa_circ_0005519 host gene) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…anti-CIRC was used for further research owing to its higher knockdown efficiency. The designed siRNA should specifically aim to hsa_circ_0005519, to avoid any interference with its linear host gene [ 16 ]. Notably, the siRNAs in this study showed no effects on expression of SNX13 mRNA (hsa_circ_0005519 host gene) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of proliferative vitreoretinopathy is closely related to the epithelial-mesenchymal transition in retinal pigment epithelium cells, which is characterized by the downregulation of E-cadherin and the upregulation of N-cadherin. After the epithelial-mesenchymal transition, the expression levels of E-cadherin and keratin were decreased, whereas the expression levels of α-smooth muscle actin (α-SMA) and fibronectin were increased [19][20] . Elevated expression of E-cadherin is reportedly sufficient to inhibit epithelial-mesenchymal transition and proliferation in retinal pigment epithelium cells; this inhibits transforming growth factor (TGF)-β1-induced apoptosis, thereby delaying RRD progression to proliferative vitreoretinopathy [21] .…”
Section: Protein-protein Interaction Networkmentioning
confidence: 99%
“…Moreover, macrophages have been identified as the main source of myofibroblasts via macrophage-myofibroblast transition, thereby promoting renal fibrosis [60]. It has also been shown that exosomes from high glucose-treated macrophages promote RTECs to switch to a more pro-fibrosis phenotype via releasing long non-coding RNAs [61]. However, the role of exosomes in mediating intercellular communication requires further investigation.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Exosomes from high glucose-treated macrophage promote RTECs to switch to a more pro-fibrosis phenotype via releasing long non-coding RNAs [61] 6. Potential Therapeutics for DN by Targeting Macrophages…”
Section: Macrophage Exosomes and Rtecs Lncrnasmentioning
confidence: 99%